2010
DOI: 10.1242/dmm.004234
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of sestrin 2 induces TGF-β signaling and partially rescues pulmonary emphysema in a mouse model of COPD

Abstract: SUMMARY Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Cigarette smoking has been identified as one of the major risk factors and several predisposing genetic factors have been implicated in the pathogenesis of COPD, including a single nucleotide polymorphism (SNP) in the latent transforming growth factor (TGF)-β binding protein 4 (Ltbp4)-encoding gene. Consistent with this finding, mice with a null mutation of the short splice variant of Lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 41 publications
4
52
0
2
Order By: Relevance
“…In addition, sestrin 2 inhibits mammalian target of rapamycin (mTOR) signaling through a redox-independent mechanism, by activating AMP-activated protein kinase (AMPK) and phosphorylating tuberous sclerosis protein 2 (TSC2) (5). Although sestrin 2 knockout mice are reported to be fully viable and do not display any gross developmental abnormalities (30), a recent study (19) has shown that deletion of sestrin 2 exacerbates obesity-induced mTOR activation, glucose intolerance, insulin resistance, and hepatosteatosis.…”
mentioning
confidence: 99%
“…In addition, sestrin 2 inhibits mammalian target of rapamycin (mTOR) signaling through a redox-independent mechanism, by activating AMP-activated protein kinase (AMPK) and phosphorylating tuberous sclerosis protein 2 (TSC2) (5). Although sestrin 2 knockout mice are reported to be fully viable and do not display any gross developmental abnormalities (30), a recent study (19) has shown that deletion of sestrin 2 exacerbates obesity-induced mTOR activation, glucose intolerance, insulin resistance, and hepatosteatosis.…”
mentioning
confidence: 99%
“…Sesn2 overexpression in 293 cells stimulates cell death [119]. Sestrins also modulate cell viability under stress condition, protecting from oxidative stress, but supporting cell death in response to genotoxic stress [119,123,143,147]. Cell death in response to -irradiation is regulated in an AMPK-dependent manner and Sesn2 plays a major role in regulation of AMPK phosphorylation in response to genotoxic stress [40,41,143].…”
Section: Regulation Of Ampk-tor Signaling By Sestrinsmentioning
confidence: 99%
“…It was shown that R-Smads, Smad1-5, are substrates of TGF receptors, activated by TGF, while others are activated by other members of the TGF family via interaction with relevant receptors. Phosphorylated Smad2 and Smad3 form heteromeric complexes with Smad4, which translocate to the nucleus where they bind Smad-dependent promoters and activate expression of a number of genes such as -smooth muscle actin (SMA), connective tissue growth factor (CTGF) and matrix metalloproteinase 2 (MMP2) involved in regulation of cell growth, differentiation and migration [147,152]. TGF also controls other signaling pathways through RhoA, Cdc42, Rac1, Ras, PI3K, PP2A, MEKK1, TAK1 and DAXX proteins.…”
Section: Regulation Of Tgf Signaling By Sesn2mentioning
confidence: 99%
See 2 more Smart Citations